DAMPAK KEMAJUAN IPTEK BAGI GENERASI X,Y, Z DALAM PERSPEKTIF ETIKA KRISTEN - Samuel Tampubolon (JURNAL IMPARTA, 2024)
Science and technology (IPTEK) continues to develop. These developments will certainly produce changes that will be felt directly by humans themselves, both as individuals and groups. In its development, science and technology has two impacts at once, namely positive impacts and negative impacts. Until now, the dynamics of pros and cons of the development of science and technology continue to take place in the midst of society. These developments will bring new challenges and demand new ways of working. Some are pro and some are con, and some are examined from a religious perspective to measure what can be done and what should not be done. However, in this paper, the author discusses the impact of the progress and development of science and technology from the perspective of Christian ethics. The author understands that the application of science and technology without ethics will cause serious problems. Christian ethics is here to provide ethical and normative boundaries so that the progress and development of science and technology does not violate the human side which then has a destructive impact on the sustainability of human life.